Use of non-vitamin K antagonists oral anticoagulants in atrial fibrillation patients on dialysis - Li, Wenhao; Zhou, Yanxia; Chen, Siqi; Zeng, Dewang; Zhang, Haidong (Frontiers in Cardiovascular Medicine, 2022)
Background Non-vitamin K antagonist oral anticoagulants (NOACs) showed a benefit-risk profile superior to that of warfarin in atrial fibrillation (AF) patients with mild to moderate chronic kidney disease. However, the effectiveness and safety of NOACs in AF patients with end-stage renal disease (ESRD) on dialysis remain unclear. Therefore, we performed a meta-analysis regarding the effect of NOACs vs. warfarin in AF patients undergoing dialysis. Methods A search of the Pubmed and EMBASE databases until November 2021 was performed. Adjusted risk ratios (RRs) and 95%confidence intervals (CIs) were pooled by a random-effects model with an inverse variance method. Results Six studies involving 3,744 NOAC- and 26,973 warfarin- users were deemed to meet the criteria. In the pooled analysis, the use of mixed NOACs had similar incidences of effectiveness and safety outcomes compared with warfarin use. And factor Xa inhibitors (rivaroxaban or apixaban) did not have significantly better effectiveness than warfarin. For the safety outcomes, the use of factor Xa inhibitors was associated with a reduced risk of gastrointestinal bleeding (RR = 0.81, 95% CI 0.70–0.95), but not major bleeding and intracranial bleeding. Conclusion Compared with warfarin, the use of NOACs, especially factor Xa inhibitors (rivaroxaban or apixaban), showed at least similar effectiveness and safety outcomes in AF patients on dialysis.